Not All Catholic Schools Are Private Schools : Does It Matter for Student Performance? - Wodon, Quentin (Taylor and Francis, 2022)
National student assessments from Uganda suggest low levels of proficiency for students in primary and secondary schools. This is confirmed by data for primary schools from the 2013 Service Delivery Indicators survey. The data are used in this article to conduct an assessment of factors affecting student performance. A unique feature of the data is that comparisons can be made not only between public and private schools, but also between Catholic and non-Catholic schools, with most of the Catholic schools being public schools. The analysis looks at student performance on tests for English, numeracy, non-verbal reasoning, and the student’s overall score for the three dimensions combined. Explanatory factors include a wide range of school, teacher, child, and community characteristics. After controlling for these factors, students in private schools, Catholic or not, tend to perform better than those in public schools, Catholic or not. By contrast, differences between Catholic and non-Catholic schools, especially when the schools are public, appear to matter less for student performance.